Pola Pengkaderan Ulama di Sulawesi Selatan (Studi pada Program Ma’had Aly Pondok Pesantren As’adiyah Sengkang Kabupaten Wajo) - Idham Idham (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This article aims to elaborate the pattern of regeneration of Islamic scholars (ulama) in South Sulawesi by focusing on the study of Ma’had Aly As’adiyah Sengkang Wajo. In the search, a qualitative approach was used. Data collecting was done through interviews, observation, literature study and documentation. The results of the research indicate that the regeneration of Islamic scholars in South Sulawesi had been long conducted in some Pondok Pesantren (Islamic Boarding Schools). This study finds out that the regeneration of Islamic scholars was provided with a certain medium in a special program. The existence of Pondok Pesantren As’adiyah Sengkang by implementing the regeneration of Islamic scholars through Ma’had Aly caused Pondok Pesantren As’adiyah Sengkang to be one of 13 organizers of Ma’had Aly program that was given an operational license by the Ministry of Religious Affairs of the Republic of Indonesia.